2018
DOI: 10.3389/fmed.2018.00189
|View full text |Cite
|
Sign up to set email alerts
|

Objective vs. Subjective Health in Very Advanced Ages: Looking for Discordance in Centenarians

Abstract: Background: Living beyond 100 years of age is associated with several functional and health constraints but their impact depends on one's perception of the situation. Associations between self-rated health (SRH) with sociodemographic and psychosocial variables have been explored in several studies, revealing that one's health appraisal depends of factors beyond the objective health condition. There is a large body of literature concerning SRH in later life but lack of evidence about centenarians' perception of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…As we can understand from the work done by Cheng et al (2019), the various studies conducted on longevity are too heterogenous, and they often do not consider that how a person perceives her/his mental and/or physical health depends on factors that often are beyond the objective health condition. As Ribeiro points out, "There is a large body of literature concerning SRH (self-rated health) in later life but lack of evidence about centenarians' perception of health and its associated factors, which could increase the available knowledge on the strengths and resources individuals in very advanced ages have for facing daily life limitations" (Araújo et al, 2018).…”
Section: O M M E N T a R Ymentioning
confidence: 99%
“…As we can understand from the work done by Cheng et al (2019), the various studies conducted on longevity are too heterogenous, and they often do not consider that how a person perceives her/his mental and/or physical health depends on factors that often are beyond the objective health condition. As Ribeiro points out, "There is a large body of literature concerning SRH (self-rated health) in later life but lack of evidence about centenarians' perception of health and its associated factors, which could increase the available knowledge on the strengths and resources individuals in very advanced ages have for facing daily life limitations" (Araújo et al, 2018).…”
Section: O M M E N T a R Ymentioning
confidence: 99%
“…Given the multi‐dimensional nature of health, a gold‐standard objective health scale is unrealistic. Previous studies have operationalized objective health as the amount of disease diagnoses a patient has received, combined with measures of functional capacity, such as Instrumental Activities of Daily Living (IADLs) and Basic Activities of Daily Living (Araújo, Teixeira, Ribeiro, & Paúl, 2018). An issue with such measures, however, is that health is more complex than just disease and functional status.…”
Section: Introductionmentioning
confidence: 99%
“…Although self-rated health among older adults has been associated with the presence of chronic noncommunicable diseases and their complications (Confortin et al, 2015), recent studies have indicated that health self-perception in very-old older adults may be related to aspects beyond the presence of chronic diseases and the functional disability, such as the perception of successful aging, psychological resilience, and life satisfaction (Araújo et al, 2018; Carstensen et al, 2011). Thus, the direct relationship between physical function and health perception observed in younger-old older adults is not usually linear among the very-old older adults, suggesting that the factors that influence the health of the younger age group, paradoxically, do not have the same impact for older adults over 80 years old (Gondo, 2012).…”
Section: Introductionmentioning
confidence: 99%